2015
DOI: 10.1016/j.hrthm.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Complex excitation dynamics underlie polymorphic ventricular tachycardia in a transgenic rabbit model of long QT syndrome type 1

Abstract: BACKGROUND Long QT syndrome type 1 (LQT1) is a congenital disease arising from a loss of function in the slowly activating delayed potassium current IKs, which causes early afterdepolarizations (EADs) and polymorphic ventricular tachycardia (pVT). OBJECTIVE The purpose of this study was to investigate the mechanisms underlying pVT using a transgenic rabbit model of LQT1. METHODS Hearts were perfused retrogradely, and action potentials were recorded using a voltage-sensitive dye and CMOS cameras. RESULTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 25 publications
4
39
3
Order By: Relevance
“…; Kim et al . ). More recently, a novel transgenic rabbit LQT5 model, produced by cardiac specific expression of a KCNE1 mutant that functions as a dominant negative, was described with markedly altered repolarization reserve attributed to changes in both I Ks and I Kr (Major et al .…”
Section: Experimental Models In the Study Of Cardiac K+ Channel Functionmentioning
confidence: 99%
“…; Kim et al . ). More recently, a novel transgenic rabbit LQT5 model, produced by cardiac specific expression of a KCNE1 mutant that functions as a dominant negative, was described with markedly altered repolarization reserve attributed to changes in both I Ks and I Kr (Major et al .…”
Section: Experimental Models In the Study Of Cardiac K+ Channel Functionmentioning
confidence: 99%
“…[4,[15][16][17][18]. They are an important cause of ventricular arrhythmias in the LQTS, but the mechanisms by which EADs at the cellular scale cause arrhythmias such as TdP are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the lack of knockin animal models that replicate the LQTS phenotype has to date limited the ability to dissect the arrhythmogenic mechanisms further. Data from transgenic rabbits, 71 despite the limitation of the presence of multiple, randomly inserted copies of the mutant gene in the genome of the animals, have recently been instrumental to support a novel view on the arrhythmogenesis in LQTS by Chang et al 72 These authors developed an in silico model of prolonged repolarization in 2-dimensional cardiac tissue by increasing I Ca and I ks to induce action potential prolongation and early after depolarizations. In this model, they demonstrated that arrhythmogenesis is caused by 2 types of spiral waves: short cycle rapid I Na generated waves ( Figure 5A) and long cycle, slow L-type calcium current (I Ca ) generated spiral waves ( Figure 5B).…”
Section: Arrhythmogenic Mechanismsmentioning
confidence: 99%
“…72 Interestingly, in this model, the alternation of the 2 types of spiral waves generated a torsades des pointes-like ECG. Subsequently Kim et al 71 investigated arrhythmogenesis in the LQT1 transgenic rabbit models inducing polymorphic VT with isoproterenol and they demonstrated the presence of complex focal excitations occurring in both ventricles and causing oscillations of the QRS complexes consistent with multiple early after depolarizations-generated foci. They also showed a bimodal distribution of the action potential supporting the coexistence of 2 types of excitation that contribute to arrhythmogenesis: I Na -mediated fast conduction and I Ca -mediated slow conduction coexist supporting the biexcitability hypothesis by Chang et al…”
Section: Arrhythmogenic Mechanismsmentioning
confidence: 99%